SISTEM APLIKASI LOKASI KEAMANAN KENDARAAN MENGGUNAKAN GPS (GLOBAL POSITION SYSTEM) BERBASIS WEB - Alam, Syahirun; Januansyah (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
Parepare city is a developed city which requires its people to have high mobility for the sake of work demands or daily activities. The higher the need for transportation, the higher the motor theft crime. Since 2019 until now there have been around 69 cases of theft and only a few have been found by the police, it is because there is no Gps device on the vehicle so that it cannot track the location of the lost vehicle. GPS tracking is a system that allows users to track the position of motorized vehicles in real time. The type of research that will be carried out in this study is to create a vehicle security location application system using a web-based GPS (global position system). This application can monitor the location of the vehicle and can also control the engine and horn on the vehicle remotely. Testing the system that has been made Black Box, it is found that the functional application runs well in accordance with the design made.